ANALYSIS OF THE FEASIBILITY OF SCIENCE LEARNING MULTIMEDIA BASED ON SCIENTIFIC INQUIRY - Hasanah, Uswatun; Edwita, Edwita; Januar, Ahmad (Balai Besar Guru Penggerak Jawa Timur, 2023)
Scientific inquiry-based science learning multimedia plays a very important role in fostering students' critical thinking skills. This study aims to analyze the feasibility of the media that has been made based on input from experts. This study involved 15 experts consisting of material experts, linguists, media experts, and learning design experts as well as educational practitioners. Based on calculations using Aiken's V, it shows that the entire index V > 0.79 (V table Aiken). This proves that all items contained in the questionnaire represent the construct being measured and are said to have adequate content validity. In addition, input from experts was also analyzed qualitatively. Thus, interactive multimedia products are said to be valid for use as science learning media. This media can be a recommendation for teachers to teach science, especially in abstract material and can train students' critical thinking skills.AbstrakMultimedia pembelajaran IPA berbasis scientific inquiry sangat berperan dalam menumbuhkan keterampilan berpikir kritis siswa. Adapun penelitian ini bertujuan untuk menganalisis kelayakan media yang telah dibuat berdasarkan masukan dari para ahli. Penelitian ini melibatkan 15 ahli yang terdiri dari ahli materi, ahli bahasa, ahli media, dan ahli desain pembelajaran serta praktisi pendidikan. Berdasarkan perhitungan menggunakan Aiken’s V menunjukkan bahwa seluruh indeks V > 0.79 (V tabel Aiken). Hal ini membuktikan bahwa seluruh item yang terdapat pada kuesioner mewakili konstrak yang diukur dan dikatakan memiliki validitas isi yang memadai. Di samping itu masukan dari para ahli juga dianalisa secara kualitatif. Dengan demikian, produk multimedia interaktif dikatakan valid digunakan sebagai media pembelajaran IPA. Media ini dapat menjadi rekomendasi bagi para guru untuk membelajarkan IPA khususnya pada materi yang abstrak dan dapat melatih keterampilan berpikir kritis siswa.